PENGARUH DISIPLIN KERJA, MOTIVASI, DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT XYZ - Joni Efendi (JURNAL MITRA MANAJEMEN, 2022)
The purpose of this research was to determine The Influence Of Labor Discipline, Motivation, and Training On Employees Performance at PT XYZ. The method used in this research using questionnaries and distributed to the PT XYZ. Based on the number of questionnaeries returned, determined the sample in this research were 70 respondent. The analysis is done by looking for the effect, determination and the relationship between variables using SPSS 23.0 for windows. The result showed that: 1). tcount= 3.596 > ttable= 1.996, H1 is a accept, Labor Discipline (X1) has significant influence on Employees Performance (Y), 2). tcount= 3.562 > ttable= 1.996, H2 is a accept, Motivation (X2) has significant influence on Employees Performance (Y), 3). tcount= 5.462 > ttable= 1.996, H3 is a accept, Training (X3) has significant influence on Employees Performance (Y), 4). Fcount = 11.723 > Ftable = 2.744, H4 is accept, Labor Discipline (X1), Motivation (X2), and Training (X3) On Employees Performance (Y). Keywords:Labor Discipline, Motivation, Training, Employees Performance